2018
DOI: 10.1212/nxi.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to vaccines is maintained in patients treated with dimethyl fumarate

Abstract: Objectives:To investigate the immune response to vaccinations in patients with relapsing forms of MS treated with delayed-release dimethyl fumarate (DMF) vs nonpegylated interferon (IFN).Methods:In this open-label, multicenter study, patients received 3 vaccinations: (1) tetanus-diphtheria toxoid (Td) to test T-cell–dependent recall response, (2) pneumococcal vaccine polyvalent to test T-cell–independent humoral response, and (3) meningococcal (groups A, C, W-135, and Y) oligosaccharide CRM197 conjugate to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 21 publications
5
78
0
1
Order By: Relevance
“…A recent study with DMF in multiple sclerosis patients has reported that patients mounted an adequate immune response to inactivated vaccines. 66 There is no evidence of an impaired immune response to vaccination and in daily clinical practice, patients are not advised to suspend FAE treatment before vaccination with inactivated (as against live) vaccines.…”
Section: Can Patients Receive Vaccinations While Being Treated With Dmf?mentioning
confidence: 99%
“…A recent study with DMF in multiple sclerosis patients has reported that patients mounted an adequate immune response to inactivated vaccines. 66 There is no evidence of an impaired immune response to vaccination and in daily clinical practice, patients are not advised to suspend FAE treatment before vaccination with inactivated (as against live) vaccines.…”
Section: Can Patients Receive Vaccinations While Being Treated With Dmf?mentioning
confidence: 99%
“…33 There is insufficient evidence to support or refute whether individuals with MS receiving DMF are likely to differ in response to TT, diphtheria toxoid, pneumococcal, or meningococcal vaccination compared with participants with MS receiving IFN-β. 34 There is insufficient evidence to support or refute whether individuals with MS receiving alemtuzumab are likely to differ in response to Haemophilus influenzae type b, meningococcal, or pneumococcal polysaccharide vaccines compared with HCs. 35 There is insufficient evidence to support or refute whether individuals with MS receiving IFN-β therapy are likely to differ in response to BCG vaccination compared with individuals with MS not receiving such treatment.…”
Section: Tetanus Toxoid Vaccinationmentioning
confidence: 99%
“…An IFN-β-controlled study examined the effectiveness of vaccination in MS patients treated with dimethyl fumarate (DMF) [107]. There were no significant differences in T-cell-dependent recall response (both 68% of DMF-treated patients and 73% of IFN-β-treated patients had ≥2-fold increase in IgG), lower but non-significant T-cell independent humoral response (66% of DMF-treated vs. 79% IFN-β-treated) and no differences in the response towards neoantigen, with 53% of both DMF-and IFN-β-treated MS patients developing immunity towards meningococcal C [107]. A similar vaccine design was employed for a pilot study in 25 MS patients treated with alemtuzumab, which were compared to literature controls [108].…”
Section: The Remaining Studies Utilize a Range Of Vaccines That Wouldmentioning
confidence: 99%